A108: Linking Exercise, Activity and Pathophysiology in Childhood Arthritis: An Innovative Canadian Knowledge Translation Strategy. Issue 11 (March 2014) - Gibbon, Michele; Tucker, Lori B.; Feldman, Debbie Ehrmann; McKay, Heather A.; Sims‐Gould, Joanie; Stinson, Jennifer N.; Stringer, Elizabeth; Tse, Shirley M. L.; ,; Duffy, Ciarán M.
Abstract : Background/Purpose: We implemented a novel knowledge translation (KT) initiative called the LEAP Ambassador Program to disseminate findings from the "Linking Exercise, Activity and Pathophysiology (LEAP) in Children with JIA study." The main hypothesis of the study is that increased levels of physical activity will improve the outcomes (such as quality of life) of youth with juvenile idiopathic arthritis (JIA). The aim of this initiative is to inspire youth with JIA to be physically active through the creation of a community of athletes and youth with JIA, who model different levels of physical activity. Methods: The LEAP Ambassador program was developed by the LEAP study program manager and approved by the LEAP Steering Committee. Various levels of athletes, ranging from international, national, college/university level, and local LEAP study participants (youth with JIA, aged 8–16 years), were sought. Individuals agreeing to participate signed consent for use of their personal photo(s) and interview on the LEAP website (www.leapjia.com ). Participants were asked to provide a photo of themselves involved in a sport or physical activity, and to answer 6 brief questions about their motivation to engage in sport/physical activities, in the face of disease flares and/or injuries. Each of the participating LEAP sites was encouraged to seek local LEAP ambassadors through their clinics and community connections, to ensure representation across the country. Results: To date, 15 LEAP ambassadors have been engaged in the program, including 3 international/national level athletes, 2 college/provincial level athletes and 10 youth with JIA. Different levels of physical activity and sports, including freestyle skiing, soccer, walking, horseback riding, speed skating, hockey, cycling and rowing, have been represented. The 10 youth with JIA who have agreed to be LEAP ambassadors come from across the country. Both English and Frenchspeaking ambassadors have been included. Conclusion: The LEAP ambassador program is a unique KT initiative aimed at developing a robust community across the country to support the research messages of the LEAP study, relating to the promotion of physical activity in youth with arthritis. A supportive network is being developed, in which athletes act as role models, inspiring youth with JIA to engage in physical activity, and the youth themselves encourage and motivate each other through shared experiences. Future plans include expansion of the program to include more athletes and youth with JIA, and increased use of social media to connect patients and athletes. An evaluation of the effectiveness of the program is also planned.